2010
DOI: 10.1213/ane.0b013e3181cb3f5f
|View full text |Cite
|
Sign up to set email alerts
|

Resistive-Polymer Versus Forced-Air Warming: Comparable Efficacy in Orthopedic Patients

Abstract: RP warming performed as efficiently as FA warming in patients undergoing orthopedic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 28 publications
1
31
1
1
Order By: Relevance
“…But since lower-body warming is often clinically required, heating systems should ideally work in both upper-and lower-body modes. Brandt and colleagues found that core and meanskin temperatures were comparable with the Hot Dog system and forced-air in patients having 90-min long extremity surgery [29]. They compared two 'multiposition pads' having a total warming area similar to that provided by an upper-body forced-air cover.…”
Section: Discussionmentioning
confidence: 99%
“…But since lower-body warming is often clinically required, heating systems should ideally work in both upper-and lower-body modes. Brandt and colleagues found that core and meanskin temperatures were comparable with the Hot Dog system and forced-air in patients having 90-min long extremity surgery [29]. They compared two 'multiposition pads' having a total warming area similar to that provided by an upper-body forced-air cover.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when evaluated against forced-air warming, an early non-clinical investigation with healthy volunteers showed that the heat transfer achieved from resistive heating was significantly greater [92]. However, the superiority of resistive heating over forced-air warming in this non-clinical study has not been reproduced in clinical trials, with the majority showing equivalence [54,55,[93][94][95][96] between devices and three favouring forced-air warming (Tables 3 and 4) [56,57,97].…”
Section: Resistive Heatingmentioning
confidence: 90%
“…This includes patients undergoing general anaesthesia [54,55,[93][94][95] and neuraxial blockade [96]. As heat transfer from resistive warming devices occurs primarily via conduction, the surface area available for warming plays an important role in devices' performance.…”
Section: Resistive Heatingmentioning
confidence: 99%
“…If the blower is used without the designated blanket, e.g., by putting the tube under the patient ' s duvet, it can cause severe burns ( " hosing " ) [85,122] . Other intrinsic limitations of forced-air warming are the potentially disturbing noise of the fan and the increased temperature in proximity to the device [10] . Further concerns exist about bacterial contamination of the forced-air system [110] .…”
Section: Forced-air Warmingmentioning
confidence: 99%
“…The heat transfer depends mainly on the contact area between blanket and skin, and it is not important if the blanket heats with circulating water [14,36,54] , with resistive carbon fibres [35,64,91] or polymers [10,63] . In all areas, without direct contact between blanket and skin, only radiation contributes to warming.…”
Section: Conductive Warming -Over-body Blanketsmentioning
confidence: 99%